Ingresos y gastos del año 2020-2021 ocasionados por la pandemia del COVID-19 en el comisariato Jr. Marisol-Cantón Pedro Carbo-Guayas. - Valdivieso Galarza, Andreina Lilibeth (2022)
This case study is carried out with the aim of analyzing the economic situation of its income and expenses caused by the COVID-19 pandemic; through financial tools to determine the factors that influence the Jr. Marisol curatorship. In which the pandemic has occurred throughout humanity and now it is the case that we have had to live; this has caused an Ecuadorian economic crisis so there has been an unusual behavior of business. The main objective of this case study is based on the análisis of the income and expenses of the years 2020 and 2021 of the curator Jr. Marisol. Knowing that every company, whether small or large, must carry out good financial management to safeguard your company from any crisis. Research that is intended to be carried out is to know what negative and positive factors were obtained, analyzing their income and expenses and applying financial analysis to give veracity of the information obtained to know in an orderly manner the economic situation of the company. The methodology applied was quantitative, bibliographic and descriptive on the importance of the analysis of the results statements. In turn, this result obtained is the evaluation consisting of the specific analysis, which shows the economic and financial situation of the company, having in comparison the management of 2020 and 2021 already mentioned above; and also conducting a survey of the owner manager of the Jr. Marisol Commissariat located in the Pedro Carbo Canton-Guayas province..